Utility of Lesser known Homoeopathic Medicines: In Current Trends Type 2 Diabetes Mellitus (Advancements in Homeopathic Research, 2024)
The burden of diabetes is high and increasing globally,  and in developing economies like India, mainly  fueled by the increasing prevalence of overweight/ obesity and unhealthy lifestyles. In 2019, India had  an estimated 77 million people with diabetes, and  projections suggest this number will surpass 134  million by 2045. Around 57% of these individuals  are currently undiagnosed. The majority of diabetes  cases in India are Type 2, and this form of diabetes  can result in various complications affecting multiple  organs. These complications are broadly categorized  into microvascular and macrovascular complications.  These complications are a significant cause for  increased premature morbidity and mortality among  individuals with diabetes, leading to reduced life  expectancy and financial and other costs of diabetes  leading to profound economic burden on the Indian  health care system. It is noteworthy that certain lesser known homeopathic remedies demonstrate efficacy  in reducing blood sugar levels, thereby playing a  crucial role in the prevention and management of  complications associated with diabetes mellitus.
Keywords: Diabetes mellitus; Insulin; Type 2; Homeopathy